Geographies of everyday nationhood: experiencing multiculturalism in Melbourne. Issue 3 (9th August 2018) - Edensor, Tim; Sumartojo, Shanti
Abstract: In this article, we explore the geographies of nationhood manifest in everyday life, arguing that our quotidian surroundings continually reproduce the nation as we engage with them. We show that nationhood is obvious and ubiquitous in the lives of people when they are asked to attune to it, and that even when not in the forefront of attention, it partly informs how we make sense of our daily experiences. This is not to claim that nationhood is fully formed or coherent, a separate substratum waiting to be tapped into or closely defined by an identifiable symbolic repertoire, if only we pay attention. Instead, we demonstrate that nationhood is emergent in everyday life, is reproduced continuously and intimately entangled with the sensations, routines, material environments, public encounters, everyday competencies, memories, aspirations and a range of other affective and embodied qualities that comprise how we understand and inhabit our worlds. This mundane experience involves shifting between reflexive and unreflexive states, and the method we deploy ‐ photo‐elicitation ‐ is devised to draw out these oscillations and heighten the attunement of participants to the usually unreflexively apprehended taken‐for‐granted national qualities of everyday space. Here, we aim to empirically foreground the neglected spatial dimensions that characterize the experience of banal nationalism.